2019
DOI: 10.1016/j.ejvs.2019.09.443
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Clinical Outcome Of REBOA in Patients With Impending Traumatic Cardiac Arrest

Abstract: to the primary end point was analyzed. Results: Total of 300 bypasses were performed and 255 (85%) had DFUs. Mean follow up was 18.4 months. AFS was 91.4%, 62.9% and 57.4% in one month, 12 and 24 months respectively in diabetic patients and did not differ significantly from the non diabetics. There was a statistically significant increase in overall survival (p-0.045) in diabetics with a hazard ratio of 1.778 in non-diabetics after Cox regression analysis. Among the bypasses 119 (46%) were femoro-popliteal and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 0 publications
1
23
0
Order By: Relevance
“…With increased experience over time, subsequent studies have shown more successful percutaneous access [ 33 , 34 ]. Our study, similar to others, has shown that surgical cutdown is used less frequently and that use of external anatomic landmarks and palpation alone to puncture the CFA has a high rate of success [ 3 ]. This could be related to the availability of smaller and guidewire-free REBOA catheters such as the ER-REBOA™ catheter (Boerne, TX, USA), which is compatible with many 7 Fr sheaths.…”
Section: Discussionsupporting
confidence: 83%
“…With increased experience over time, subsequent studies have shown more successful percutaneous access [ 33 , 34 ]. Our study, similar to others, has shown that surgical cutdown is used less frequently and that use of external anatomic landmarks and palpation alone to puncture the CFA has a high rate of success [ 3 ]. This could be related to the availability of smaller and guidewire-free REBOA catheters such as the ER-REBOA™ catheter (Boerne, TX, USA), which is compatible with many 7 Fr sheaths.…”
Section: Discussionsupporting
confidence: 83%
“…23,24 Blind placement technique using anatomic landmarks and estimated distance has been developed for the use of REBOA in trauma patients. 25,26 This blind technique is likely adequate for use during NTCA and is currently in use in a Phase 1 clinical trial at Yale University. 27 Once in the desired position the balloon at the tip of the REBOA catheter is inflated with a radiopaque solution, fully occluding the aorta.…”
Section: Reboa Deployment During Cprmentioning
confidence: 99%
“…However, this does not per se confirm "true" cardiac arrest but may represent a state of inadequate perfusion with impending cardiac arrest. A current study demonstrated that REBOA in patients with impending cardiac arrest is feasible and showed a survival rate of 37% [3]. The international resuscitation guidelines (ERC and AHA) advocate a consistent approach to CPR on the basis of upto-date evidence and expert's consensus opinions about the use of invasive measures, including resuscitative thoracotomy (RT), in order to eliminate reversible causes of cardiac arrest in trauma patients [2,[4][5][6].…”
Section: Introductionmentioning
confidence: 99%